Does Serum Uric Acid Status Influence the Association Between Left Atrium Diameter and Atrial Fibrillation in Hypertension Patients? - Hidru, Tesfaldet H.; Tang, Yuqi; Liu, Fei; Hui, Simei; Gao, Ruiyuan; Li, Daobo; Yang, Xiaolei; Xia, Yunlong (Frontiers in Cardiovascular Medicine, 2020)
Objective: Both serum uric acid (SUA) levels and left atrium diameter (LAD) associate with AF. However, the influence of SUA status for the associated risk of AF related to LAD in hypertension patients is currently unknown. Methods: We retrospectively analyzed a hospital-based sample of 9618 hypertension patients. Standard electrocardiograms were performed on all patients and were interpreted by expert electro-physiologists. Results: Overall 1028 (10.69%) patients had AF out of 9618 patients. In men >65 years of age, the prevalence of AF in the 1st, 2nd, and 3rd tertiles of SUA among those grouped in the third tertile of LAD were 9%, 12.3%, and 21.7%, respectively. In the hyperuricemia group, the OR (95% CI) of AF for the highest tertile of LAD in men ≤65 years of age was 3.150 (1.756, 5.651; P<.001). Similarly, the hyperuricemic men in the 3rd LAD tertile had a higher likelihood of AF than those belonging to the 1st tertile. The ORs and (95% CIs) were 3.150 (1.756, 5.651; P<.001) and 5.522 (2.932, 10.400; P≤.001) for patients ≤65 and >65 years of age. An increase in SUA values was significantly associated with an increased likelihood of AF among women at the top tertiles of LAD, with the OR (95% CI)=4.593 (1.857, 11.358; P=.001). Also, men> 65 years of age with large LAD, present at the third tertile of SUA, had a higher likelihood of AF, with the OR (95% CI)=2.427 (1.039, 5.667; P<.05). Conclusion: SUA levels and LAD are associated with AF in patients with hypertension and the risk of AF associated with LAD increases among those with hyperuricemia.